Hubungan Tingkat Pengetahuan Orang Tua dengan Status Gizi Anak di Bawah 5 Tahun di Posyandu Wilayah Kerja Puskesmas Nusukan Surakarta - In'am, Miftahul; , dr. Yusuf Alam Romadhon, M.Kes; , dr. M. Shoim Dasuki, M.Kes (2016)
The children under 5th are the age group most vulnerable impaired growth and development. So that they need optimal nutrition. Parent's is a person that have role to fulfill nutrition intake. Parent's knowledge affect to nutritional status of children. Objective to know the relationship between the parent's knowledge with the nutritional status of children under 5th in Posyandu Puskesmas Nusukan working area of Surakarta This research is an observational analytic by cross sectional approach. It is carried in Posyandu Puskesmas Nusukan of Surakarta in February 2016. The sampling is conducted by purposive sampling technique which use 47 samples of BB, TB and old. The data is obtained processed using SPSS for Windows 17 and analyzed by chi-square. The statistical test of Chi-square show that there is relationship between parent's knowledge with nutritional status of children under 5th in Posyandu Puskesmas Nusukan working area of Surakarta with value P<0,001. Based on this study, can be concluded that there was relationship between parent's knowlaedge with nutritional status of children under 5th in posyandu Puskesmas Nusukan working area of Surakarta.